Pathophysiology of ischaemic stroke: insights from imaging, and implications for therapy and drug discovery - Moustafa, R R (Nature Publishing Group, 2008)
Preventing death and limiting handicap from ischaemic stroke are major goals that can be achieved only if the pathophysiology of infarct expansion is properly understood. Primate studies showed that following occlusion of the middle cerebral artery (MCA)––the most frequent and prototypical stroke, local tissue fate depends on the severity of hypoperfusion and duration of occlusion, with a fraction of the MCA territory being initially in a ‘penumbral' state. Physiological quantitative PET imaging has translated this knowledge in man and revealed the presence of considerable pathophysiological heterogeneity from patient to patient, largely unpredictable from elapsed time since onset or clinical deficit. While these observations underpinned key trials of thrombolysis, they also indicate that only patients who are likely to benefit should be exposed to its risks. Accordingly, imaging-based diagnosis is rapidly becoming an essential component of stroke assessment, replacing the clock by individually customized management. Diffusion- and perfusion-weighted MR (DWI-PWI) and CT-based perfusion imaging are increasingly being used to implement this, and are undergoing formal validation against PET. Beyond thrombolysis per se, knowledge of the individual pathophysiology also guides management of variables like blood pressure, blood glucose and oxygen saturation, which can otherwise precipitate the penumbra into the core, and the oligaemic tissue into the penumbra. We propose that future therapeutic trials use physiological imaging to select the patient category that best matches the drug's presumed mode of action, rather than lumping together patients with entirely different pathophysiological patterns in so-called ‘large trials', which have all failed so far.